DETERMINASI EKSPOR, INVESTASI, DAN PRODUKTIVITAS TERHADAP PERTUMBUHAN DI SEKTOR PRIMER DAN SEKUNDER INDONESIA PERIODE 2005-2014 - Santi Rizkiyanti; Lilis Yuliati; Moehammad Fathorrazi (MediaTrend, 2016)
Economic growth is an indicator to determine the overall of economy condition. There are some leading sectors that become jump-start economic growth of a country. They are the primary sectors consist of agriculture and mining, and the secondary sector is processing industry. This research aims to understand the impact of export, investment, and productivity to economic growth in Indonesia’s primary and secondary sectors. This research uses the panel data regression method (Panel Least Square). From the estimation result, fixed effect is the best model of the model selection using the Chow test. It is shown by partial test (t-test) that exports, investment and productivity have a positive and significant impact to economic growth in Indonesia’s primary and secondary sectors. In a cross-sectoral, relative estimation results indicate that exports of agricultural and industrial have positive impact on the growth while the mining sector has a negative impact. In other side, investment and productivity of primary sectors (agricultur and mining) have negatif impact on growth while the industrial has positive impact.